A test of the interpersonal-psychological theory of suicide among arrested domestic violence offenders. (March 2017) - Wolford-Clevenger, Caitlin; Brem, Meagan J.; Elmquist, JoAnna; Florimbio, Autumn Rae; Smith, Phillip N.; Stuart, Gregory L.
Abstract: Little is known about risk factors for suicide ideation and attempts among domestic violence offenders. Guided by the interpersonal-psychological theory of suicide, this cross-sectional study examined risk factors for suicide ideation and attempts among 312 men and 84 women arrested for domestic violence and mandated to attend batterer intervention programs. Men reported greater capability for suicide, but no gender differences were found in perceived burdensomeness and thwarted belongingness. After controlling for correlates of suicide ideation, perceived burdensomeness—but not thwarted belongingness or its interaction with perceived burdensomeness—associated with suicide ideation. Suicide attempters exhibited greater perceived burdensomeness, drug use and problems, borderline personality disorder symptoms, depressive symptoms, and suicide ideation, but not capability for suicide, than nonattempters. Gender did not moderate the associations of the IPTS constructs with suicide ideation and attempts. These findings parallel tests of the interpersonal-psychological theory in other samples. Additional work is needed to identify factors that distinguish risk for suicide ideation from risk for suicide attempts among domestic violence offenders. Highlights: We tested a theory of suicide among individuals arrested for domestic violence. Men had greater capability for suicide but more women reported suicide attempts. Perceived burdensomeness associated with suicide ideation. Suicide attempters did not exhibit greater capability for suicide than nonattempters. Attempters showed more psychiatric symptoms and burdensomeness than nonattempters.